2017
DOI: 10.1089/jpm.2016.0417
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Community-Based Palliative Care on Utilization and Cost of Acute Care Hospital Services in the Last Year of Life

Abstract: In addition to supporting people to die out of hospital, PCS was associated with reduced acute care admissions, bed days, and costs over the last year of life. The provision of high-quality palliative care in the community alleviates the burden on acute care hospitals and, thus, may partially offset public funding of this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 26 publications
1
48
0
Order By: Relevance
“…Insufficient access to or availability of skilled palliative care staff in the aged care sector in Australia can direct burden of death to acute care settings. The few community‐based initiatives implemented in Australia aiming both to deliver palliative care at home and support carers have shown a reduction in hospital use at end of life . A Cochrane review also concluded that home‐based palliative care has reduced in‐hospital death and burden of symptoms .…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient access to or availability of skilled palliative care staff in the aged care sector in Australia can direct burden of death to acute care settings. The few community‐based initiatives implemented in Australia aiming both to deliver palliative care at home and support carers have shown a reduction in hospital use at end of life . A Cochrane review also concluded that home‐based palliative care has reduced in‐hospital death and burden of symptoms .…”
Section: Discussionmentioning
confidence: 99%
“…Areas of care that were valued, but often not actualized, were consistency of home care providers; accessibility of staff; nursing and personal support for patients that matched the degree of need; and an efficient system that anticipated needs, rather than requiring constant intervention initiated by the caregiver. Although community‐based palliative care services may allow patients to remain at home and curtail hospital costs, an adequate investment is necessary to allow sufficient support for patients and caregivers, including 24‐hour support . Our study also highlights the need for better preparation and supports for caregivers in the period immediately following death, which may avert bereavement‐related distress …”
Section: Discussionmentioning
confidence: 87%
“…20 A recent study suggested that the cost of provision of specialist community palliative care services may offset the cost of hospital-based end-of-life care by reduced acute hospital admissions and bed days to the public. 21 This suggests the need for further exploration of the relationship between local hospital resources especially in areas of low deprivation and the impact on place of death for various causes.…”
Section: Discussionmentioning
confidence: 99%